Convenient Surface Treatment of LiNi0.8Co0.1Mn0.1O2 Materials Improve the Cycle Performance. Issue 2 (1st February 2022) - Tang, Jianbo; Xie, Qian; Chen, Zhishan; Tian, Ye; Zuo, Jianliang; Yang, Wei; Zheng, Wenzhi
Abstract : In this study, a suitable surface treatment was designed to optimize the cyclic quality of the LiNi0.8 Co0.1 Mn0.1 O2 . Results show that solvent treatment can wash away the lithium compounds on material's surface, which will hinder the diffusion of Li + and catalyze the decomposition of the electrolyte. Disorder degree of nickel and oxygen layers will reduce after solvent treatment, which helps Li + to embed and release better. A protective layer was found on the Solvent-treated surface of NCM811 by scanning electron microscope. Transmission Electron Microscope shows that a 3–4 nm thick Rock-salt phase NiO generated on the material surface can protect the structure stability and prevent the collapse of material with the process of charge and discharge. Through electrochemical tests show that the electrochemical performance of the material is markedly improved. Therefore, solvent treatment as a convenient modification method has specific industrial application value.